1997
DOI: 10.1091/mbc.8.8.1415
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid and microtubule-destabilizing agents stimulate fibronectin matrix assembly through Rho-dependent actin stress fiber formation and cell contraction.

Abstract: Fibronectin (FN) matrix assembly is a cell-dependent process mediated by cell surfacebinding sites for the 70-kDa amino-terminal region of FN. We have shown recently that lysophosphatidic acid (LPA) is a stimulator of FN matrix assembly. Disruption of microtubules has been shown to mimic some of the intracellular effects of LPA including the formation of actin stress fibers and myosin light chain phosphorylation. We compared the effects of microtubule disruption and LPA on FN binding and actin cytoskeleton org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
151
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 70 publications
16
151
1
Order By: Relevance
“…Originally developed as a cell permeable calpain inhibitor (Tsujinaka et al, 1988), calpeptin was serendipitously reported to stimulate actin stress fiber accumulation in fibroblasts via the inhibition of Shp-2 upstream of the small GTPase Rho (Schoenwaelder and Burridge, 1999;Schoenwaelder et al, 2000). Both the naturally occurring alkaloid colchicine and the synthetic agent, nocodazole, both inhibit microtubule assembly and promote actin stress fiber accrual in a Rhodependent manner (Bershadsky et al, 1996;Enomoto et al, 1996;Zhang et al, 1997;Liu et al, 1998). As anticipated the co-treatment of MG63 osteoblast-like cells with LPA and D3 led to a robust maturation response as supported by a clear, synergistic (Fig 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Originally developed as a cell permeable calpain inhibitor (Tsujinaka et al, 1988), calpeptin was serendipitously reported to stimulate actin stress fiber accumulation in fibroblasts via the inhibition of Shp-2 upstream of the small GTPase Rho (Schoenwaelder and Burridge, 1999;Schoenwaelder et al, 2000). Both the naturally occurring alkaloid colchicine and the synthetic agent, nocodazole, both inhibit microtubule assembly and promote actin stress fiber accrual in a Rhodependent manner (Bershadsky et al, 1996;Enomoto et al, 1996;Zhang et al, 1997;Liu et al, 1998). As anticipated the co-treatment of MG63 osteoblast-like cells with LPA and D3 led to a robust maturation response as supported by a clear, synergistic (Fig 2B).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated above, Rho-dependent cytoskeletal reorganizations have been shown by several groups to be essential for FN matrix deposition by ®broblasts (Christopher et al, 1997;Wu et al, 1995;Zhang et al, 1997;Zhong et al, 1998). This ®nding prompted us to determine whether the inhibitors that diminished deposition of FN matrix by c-Cbl-overexpressing v-Abl-transformed ®broblasts and adhesion of these cells to a non-treated surface (see Figure 6) could also inhibit spreading of these cells in culture.…”
Section: Role Of Rho-family Gtpases In C-cbl-induced Effects In V-ablmentioning
confidence: 90%
“…Considering that Rho-dependent contractility was recently shown to be essential for the assembly of FN matrix by ®broblasts (Christopher et al, 1997;Wu et al, 1995;Zhang et al, 1997;Zhong et al, 1998), we decided to determine whether an increase in spreading of v-Abltransformed ®broblasts caused by c-Cbl overexpression facilitated FN matrix deposition by these cells through the activation of small GTPases regulating cytoskeletal rearrangements. First, we directly evaluated activities of several such GTPases in v-Abl-transformed ®bro-blasts using precipitation of their GTP-bound forms followed by speci®c immunoblotting.…”
Section: Effects Of C-cbl On the Activity Of Rho-family Gtpases In V-mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of agonists including phospholipid products (Zhang, Magnusson et al 1997;Huang, Subbaiah et al 2005) and bioactive peptides (Garcia, Siflinger-Birnboim et al 1986;van Nieuw Amerongen, Draijer et al 1998;Petrache, Verin et al 2001;Moy, Blackwell et al 2002;Birukova, Adyshev et al 2005) increase vascular endothelial permeability, which my lead to alveolar flooding and pulmonary edema. However, much smaller number of bioactive molecules capable of enhancing endothelial barrier properties have been reported so far (Garcia, Liu et al 2001;Liu, Schaphorst et al 2002;VouretCraviari, Bourcier et al 2002;Birukov, Bochkov et al 2004;Kolosova, Mirzapoiazova et al 2005), and signaling mechanisms underlying these barrier protective effects have been a major focus of ongoing studies (Lee, Lee et al 2000;Garcia, Liu et al 2001;Vouret-Craviari, Bourcier et al 2002;Birukov, Leitinger et al 2004;Dudek, Jacobson et al 2004;Kolosova, Mirzapoiazova et al 2005;Mehta, Konstantoulaki et al 2005;Singleton, Dudek et al 2005).…”
Section: Introductionmentioning
confidence: 99%